Network Externalities in Telecommunication Industry: An Analysis of Serbian Market - Trifunović, Dejan; Mitrović, Đorđe (Industrija, 2016)
This paper deals with network competition and provides empirical analysis of market concentration, network and call externalities, access pricing, price discrimination and switching costs in Serbian mobile phone telecommunications market. It is shown that network externalities governed the expansion of this market until 2008. Upon entry of VIP incumbents didn’t engage in predatory behaviour towards entrant aiming to benefit from locked-in users. The policy of mobile phone number portability reduced on-net prices and substantially increased consumer’s surplus. In contrast to some previous research, this policy was pro-competitive in Serbia. We have also determined that users of the network with the largest market share benefit the most from call externalities. Finally, one network does not price discriminate between outgoing and incoming roaming calls, which implies that users of this network have higher level pecuniary externalities in roaming compared to users of price discriminating networks.